In memoriam / Alice Winn. - Winn, Alice (Alice Mary Felicity), 1992- (Viking, 2023)
It's 1914, and talk of war feels far away to Henry Gaunt, Sidney Ellwood and the rest of their classmates, safely ensconced in their idyllic boarding school in the English countryside. At seventeen, they're too young to enlist, and anyway, Gaunt is fighting his own private battle - an all-consuming infatuation with his best friend, the dreamy, poetic Ellwood - not having a clue that Ellwood is in love with him, always has been. When Gaunt's German mother asks him to enlist as an officer in the British army to protect the family from anti-German attacks, Gaunt signs up immediately, relieved to escape his overwhelming feelings for Ellwood. The front is horrific, of course, and though Gaunt tries to dissuade Ellwood from joining him on the battlefield, Ellwood soon rushes to join him, spurred on by his love of Greek heroes and romantic poetry. Before long, their classmates have followed suit.